2015
DOI: 10.1002/cjce.22350
|View full text |Cite
|
Sign up to set email alerts
|

Influence of drying temperature and atmosphere on the mechanical strength of iron‐ore agglomerates and sodium silicates for application in sintering processes

Abstract: This paper presents the influence of drying temperature and atmosphere on the mechanical strength of iron-ore agglomerates and sodium silicates. Mixtures of different pellet feed and sodium silicates were produced with a ball disc and cured at various temperatures. The resulting products exhibited sufficiently high mechanical strength to be transported over long distances and handled until their use in sintering processes. The agglomerates were dried/cured at temperatures between 100-550 8C and in gaseous atmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…It was reported that the drying temperature of agglomerates had an important influence on the consolidation of sodium silicate. The dehydration of sodium silicate binder in less than 550  C did not provide total insolubility of the sodium silicate in water [18,34]. Therefore, the difference between the initial and the post compressive strength of the granules might be caused by the structure weakening of sodium silicate during the water immersion experiment, which was further confirmed by the difference of Si content in the solution after water immersion experiments for different granules (Table S2).…”
Section: Effect Of the Binder Concentration On The Properties Of Compmentioning
confidence: 76%
See 1 more Smart Citation
“…It was reported that the drying temperature of agglomerates had an important influence on the consolidation of sodium silicate. The dehydration of sodium silicate binder in less than 550  C did not provide total insolubility of the sodium silicate in water [18,34]. Therefore, the difference between the initial and the post compressive strength of the granules might be caused by the structure weakening of sodium silicate during the water immersion experiment, which was further confirmed by the difference of Si content in the solution after water immersion experiments for different granules (Table S2).…”
Section: Effect Of the Binder Concentration On The Properties Of Compmentioning
confidence: 76%
“…This water resistance offers significant advantages over water soluble binders used in other studies particularly when considering deployment of the technology in wetter climates. Such inorganic binders have been used successfully to consolidate fines or small particles into larger 6 units in the processes of agglomerating bentonite, detergent, iron ore, silica and coal [18,19,20]. In this study, we have investigated the possibility of using an inorganic silicatebased binder in a drum granulation process for the production of bio-waste granules using compost as the model bio-waste.…”
mentioning
confidence: 99%
“…Soluble sodium silicate binders (water glass) have been widely used in industries due to their low cost, odorless nature, and non-toxicity. They also offer a higher level of binding performance such as strength, durability, and water resistance [ 44 ]. In a further study [ 45 ], the authors investigated the possibility of using a sodium silicate solution in a drum granulation process for the production of bio-waste granules.…”
Section: Discussionmentioning
confidence: 99%